What to keep and what to change in European electronic communications policy? - Laguna de Paz, J.C. (2012)
Examines the telecommunications industry and after almost fifteen years of full liberalisation asks the question, what should be changing in telecoms policy to further improve services, innovation and benefits to consumers. Focuses on issues such as deployment of next generation networks, greater efficiency of spectrum usage, consumer protection and the right approach to the issue of so-called network neurality.